2020
DOI: 10.1096/fasebj.2020.34.s1.06245
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Protocol for Robust Differentiation of SH‐SY5Y Cells into Neuronal‐like Cells: An in vitro Model of Human Neuronal Cultures

Abstract: The SH‐SY5Y cell line, derived from a human glioblastoma, grow and divide indefinitely under normal conditions, but have the potential to differentiate into neuronal‐like cells when treated with retinoic acid (RA). However, the extent of differentiation has been contested, leading to a variety of protocols to induce differentiation. We took a systematic approach to test the various conditions and treatments used in previously published studies to develop an optimized protocol that yields robust differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These cells also form synapses and demonstrate the ability to generate action potentials ( Johansson, 1994 , Öz and Çelik, 2016 ), and express both neurotransmitters ( Lopes et al, 2010 ) and their receptors ( Adem et al, 1987 ; Qian et al, 2018 ). Development of protocols to differentiate these cells continues with refinement of the commonly used retinoic acid protocol ( Simões et al, 2021 ) and variations to the addition of trophic support ( Jun et al, 2020 ) reported very recently.…”
Section: Introductionmentioning
confidence: 99%
“…These cells also form synapses and demonstrate the ability to generate action potentials ( Johansson, 1994 , Öz and Çelik, 2016 ), and express both neurotransmitters ( Lopes et al, 2010 ) and their receptors ( Adem et al, 1987 ; Qian et al, 2018 ). Development of protocols to differentiate these cells continues with refinement of the commonly used retinoic acid protocol ( Simões et al, 2021 ) and variations to the addition of trophic support ( Jun et al, 2020 ) reported very recently.…”
Section: Introductionmentioning
confidence: 99%